Analisis Persepsi Konsumen Atas Elemen-Elemen Lokasi dan Harga pada Pasar dan Supermarket - Muhammad Rizki Azhari; Riko Fridolend Sianturi; Aulia Arief Nasution (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2022)
This research is based on the idea that there is a difference between customers’ perception of the traditional market and modern market on location elements and price elements. The purpose of this research is to determine the perception of customers who shop or visit the Simpang Limun market and Supermarket Brastagi Medan. Teori used to analyze these problems about customer perception, location, and price. This research method is qualitative and this research intends to describe and interpret a condition. The results of the research obtained were differences between customers’ perception of the location in the Simpang Limun Market and in the Supermarket Brastagi Medan. Also the difference between customers’ perception of prices in the Simpang Limun Market and costumers in the Supermarket Brastagi Medan. Based on the results of the research has been explained, the researcher concluded that the lack of maintenance of the environment makes customers’ perception in the Simpang Limun Market far different from customers in the Supermarket Brastagi Medan and very competitive prices between Simpang Limun Market with Supermarket Brastagi Medan. Advice that can be submitted to the government is to make improvements of the location in the Simpang Limun market so that the creation of customer satisfaction and customer loyalty and for Supermarket Brastagi is to maintain and improve the quality of service based on the elements of location and price so that customers don’t move to the supermarket or other traditional markets.